Copper-catalyzed enantioselective conjugate addition of organometallic reagents to challenging Michael acceptors - Pichon, Delphine; Morvan, Jennifer; Crévisy, Christophe; Mauduit, Marc (Beilstein Journal of Organic Chemistry, 2020)
The copper-catalyzed enantioselective conjugate addition (ECA) of organometallic nucleophiles to electron-deficient alkenes (Michael acceptors) represents an efficient and attractive methodology for providing a wide range of relevant chiral molecules. In order to increase the attractiveness of this useful catalytic transformation, some Michael acceptors bearing challenging electron-deficient functions (i.e., aldehydes, thioesters, acylimidazoles, N-acyloxazolidinones, N-acylpyrrolidinones, amides, N-acylpyrroles) were recently investigated. Remarkably, only a few chiral copper-based catalytic systems have successfully achieved the conjugate addition of different organometallic reagents to these challenging Michael acceptors, with excellent regio- and enantioselectivity. Furthermore, thanks to their easy derivatization, the resulting chiral conjugated products could be converted into various natural products. The aim of this tutorial review is to summarize recent advances accomplished in this stimulating field.
Keywords: acylimidazole; N-acyloxazolidinone; N-acylpyrrole; N-acylpyrrolidinone; aldehyde; amide; copper catalysis; electron-deficient alkenes; enantioselective conjugate addition; Michael acceptor; thioester